Multifunctional ion-exchange membrane for uniform zinc deposition in highly reversible aqueous zinc-ion batteries - Juan Wu; Shuang Liu; Zilian Zhang; Yi Zheng; Jia-Lin Yang; Xing-Long Wu; Yude Wang (Chemical Engineering Journal, 2026)

Metagenomic analysis reveals the composition and sources of antibiotic resistance genes in coastal water ecosystems of the Yellow Sea and Yangtze River Delta - Xin Wang; Yude Lin; Shaoxuan Li; Jiahui Wang; Xiaohui Li; Demeng Zhang; Delin Duan; Zhanru Shao (Environmental Pollution, 2025)

Historical climate change influenced the phylogeographical patterns of the brown alga Colpomenia sinuosa in the southern China - Xiaohan Song; Jie Zhang; Yuqun Du; Shuang Li; Yiping Shen; Yude Lin; Zimin Hu; Delin Duan (Algae, 2025)
Historical climate changes significantly influenced the phylogeographical patterns of intertidal macroalgae. The brown alga Colpomenia sinuosa was common in warmer waters worldwide, providing an ideal model for genetic diversity and distribution research. C. sinuosa has abundant biomass in the coastal South China Sea, which is a well-known hotspot on marine biodiversity. Here, we analyzed its population structure and demographic history using mitochondrial cox3, atp6, and chloroplast rbcL. We detected a genetic diversity pattern of high haplotype diversity and low nucleotide diversity at the intraspecific level, and our results revealed 2 main clades within C. sinuosa with obvious genetic differentiation among most populations. Furthermore, we detected 5 genetic lineages in concatenated dataset, and the regional isolation was regarded as dominating factor for genetic differentiation. The demographic history suggested that C. sinuosa was first diverged in late Oligocene, then underwent dynamic changes during the Pleistocene. Historical vicariance caused by Pleistocene glaciation events may account for present phylogeographic pattern. Moreover, ocean current and coastal topography of northern South China Sea might participate in shaping present genetic structure. Utilizing C. sinuosa as a model material, we suggested that Dongfang in southwestern Hainan and Sanya in southern Hainan should be regarded as independent management units and give priorities to seaweed resource conservation. In the future, we’ll enlarge our study range and sample collection, and further investigate the genetic distribution pattern of C. sinuosa at larger scale. Our study enriched insights into the historical glacial influences on seaweed phylogeographical patterns, and provided theoretical evidence for seaweed management of southern China.

A novel machine learning approach for reservoir temperature prediction - Haoxin Shi; Yanjun Zhang; Yuxiang Cheng; Jixiang Guo; Jianqiao Zheng; Xin Zhang; Yude Lei; Yongjie Ma; Lin Bai (Geothermics, 2025)

Marine conditions in Andaman Sea shape the unique genetic structure of Sargassum plagiophyllum C. Agardh - Yude Lin; Jie Zhang; Yuqun Du; Shuangshuang Zhang; Li Liu; Stefano G. A. Draisma; Delin Duan (Journal of Applied Phycology, 2024)

Influence of Indo-Pacific ocean currents on the distribution and demographic patterns of the brown seaweed Sargassum polycystum in tropical east Asia - Yanshuo Liang; Shuangshuang Zhang; Changxiang Yan; Stefano G. A. Draisma; Attachai Kantachumpoo; Zhao Li; Yude Lin; Jiang Zhu; Jie Zhang; Delin Duan (Frontiers in Marine Science, 2022)
Long-distance drifting of seaweeds driven by ocean currents is an ideal model for exploring population-level genetic connectivity and phylogeographic structure. In the Indo-Pacific convergence region, we integrated phylogeographic and ocean current data and Lagrangian particle simulations to explore how the ocean currents contributed to the biogeographical patterns and population genetic connectivity of Sargassum polycystum . The oceanographic transport and direction of gene flow was in line with contemporary ocean currents. The S. polycystum geographical dispersal from glacial refugia homogenized the footprint of genetic divergence. The multidisciplinary intersection provides insights into the evolutionary history and biogeographic conservation of tropical seaweeds in the Indo-Pacific convergence region.

Enhanced adsorption properties of organic ZnCr-LDH synthesized by soft template method for anionic dyes - Jia Lin; Yude Zhang; Qian Zhang; Jinli Shang; Fuyao Deng (Environmental Science and Pollution Research, 2021)

Predicting biofilm thickness and biofilm viability based on the concentration of carbon-nitrogen-phosphorus by support vector regression - Shanshan Lin; Xinmin Wang; Yunlong Chao; Yude He; Ming Liu (Environmental Science and Pollution Research, 2016)